STRUCTURE, SPECIES COMPOSITION AND DIVERSITY OF TROPICAL MOIST EVERGREEN FORESTS IN THREE ECOLOGICAL REGIONS OF VIETNAM - Minh Toai, Pham (Journal of Forestry Science and Technology, 2016)
Results of the study on structure, species composition and diversity of tropical moist evergreen forests in three ecological regions of Vietnam showed that 61 canopy tree species at the old-growth forest in Xuan Son National Park, 62 species in Cuc Phuong NP and 58 species in Pu Mat NP were encountered. The mean densities of canopy trees varied from 425 to 477 individuals per hectare but their densities were not strongly differed among three study sites. Unlike species richness and tree density, the values of three diversity indices at the plot level of the Cuc Phuong stand were significantly lower than those of Xuan Son and Pu Mat. Within a forest stand, the IVIs of the 10 most important tree species that were ranked in this study were not very different. However, three structural parameters including height, tree canopy cover and LAI were significantly different among the three stands. Regarding relationship between DBH and Height of tree species, the Bongeret al.’s model showed at the Xuan Son stand while the natural logarithmic model was the best fit model in cases of Cuc Phuong and Pu Mat stands.